2017
DOI: 10.1093/molbev/msx158
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Evolutionary Paths to Bacterial Antibiotic Resistance Cause Distinct Collateral Effects

Abstract: When bacteria evolve resistance against a particular antibiotic, they may simultaneously gain increased sensitivity against a second one. Such collateral sensitivity may be exploited to develop novel, sustainable antibiotic treatment strategies aimed at containing the current, dramatic spread of drug resistance. To date, the presence and molecular basis of collateral sensitivity has only been studied in few bacterial species and is unknown for opportunistic human pathogens such as Pseudomonas aeruginosa. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
205
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(213 citation statements)
references
References 84 publications
(124 reference statements)
6
205
2
Order By: Relevance
“…While phage–antibiotic synergies could be driven by specific species–antibiotic combinations, it is also possible that mutation basis of adaptation plays important role. For example, in case of collateral sensitivity and cross‐resistance, it has been shown that the mutational basis of resistance to one antibiotic plays key role whether the subsequent antibiotic will have negative or neutral effect for the bacterial growth and that considerable variation can exists even between different replicate lines derived from the same selective environment (Barbosa et al., 2017). It is also likely that increasing the antibiotic concentration might change the outcome of phage–antibiotic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…While phage–antibiotic synergies could be driven by specific species–antibiotic combinations, it is also possible that mutation basis of adaptation plays important role. For example, in case of collateral sensitivity and cross‐resistance, it has been shown that the mutational basis of resistance to one antibiotic plays key role whether the subsequent antibiotic will have negative or neutral effect for the bacterial growth and that considerable variation can exists even between different replicate lines derived from the same selective environment (Barbosa et al., 2017). It is also likely that increasing the antibiotic concentration might change the outcome of phage–antibiotic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…These anti-resistance approaches exploit different features of the population dynamics, including competitive suppression between sensitive and resistance cells (14,15), synergy with the immune system (16), precise timing of growth dynamics or dosing (17,18), responses to subinhibitory drug doses (19), and band-pass response to periodic dosing (10). Resistance-stalling strategies may also exploit spatial heterogeneity (20,21,22,23,24,25), epistasis between resistance mutations (26,27), hospital-level dosing protocols (28,29), and regimens of multiple drugs applied in sequence (28,30,18,31,19,32) or combination (33,34,35,36,37,38,39,40), which may allow one to leverage statistical correlations between resistance profiles for different drugs (41,42,43,44,39,37,45,46,47,48). As a whole, these studies demonstrate the important role of community-level dynamics for understanding and predicting how bacteria respond and adapt to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, collateral profiles have also been shown to be highly heterogeneous 42,43 and often not repeatable 44 , potentially complicating the design of successful collateral sensitivity cycles. The picture that emerges is enticing, but complex; while collateral effects offer a promising new dimension for optimizing therapies, the ultimate success of these approaches will require quantitative and predictive understanding of both the prevalence and repeatability of collateral sensitivity profiles across species.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, however, our results indicate that considering longer time horizons can lead to cycles involving at least one sub-optimal step, including one to a collaterally resistant state. In addition, recent work has highlighted that collateral profiles are heterogeneous 42,43 , and optimization will therefore require incorporation of stochastic effects such as likelihood scores 44 . These likelihood scores could potentially inform transition probabilities in our MDP approach, leading to specific predictions for optimal drug sequences.…”
mentioning
confidence: 99%